2021
DOI: 10.52418/moldovan-med-j.64-6.21.03
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytes isolation from hyaline cartilage by continuous monitoring method

Abstract: Background: Articular cartilage has poor regenerative capacities. Numerous cartilage repair techniques are known, including implantation of autologous chondrocytes. Material and methods: From 18 rabbits pieces of cartilage were harvested from femoral condyle. Minced cartilage was treated with 0.25% trypsin-EDTA. In the 1st group (n=9) the cartilage was digested with 0.6% collagenase in 15 ml tubes by shaking in incubator at 37°C, 5%CO2 . In the 2nd group (n=9) digestion was performed in 25cm2 cell culture fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Jeyakumar et al noted after two weeks the redifferentiation of chondrocytes under hypoxic conditions, yielding 4% pO 2 in a culture medium enriched with platelet-rich plasma (PRP). In the study, it was observed that PRP had a stimulatory effect on the gene expression of the markers COL2A1 and SOX9 [127][128][129]. Jahr et al applied 2.5% pO 2 in the cultivation of articular chondrocytes while proving the expression of the chondrogenic markers ACAN and COL2A1 and the reduction of expression of the dedifferentiation markers COL1A1 and COL3A1.…”
Section: Activation Factorsmentioning
confidence: 99%
“…Jeyakumar et al noted after two weeks the redifferentiation of chondrocytes under hypoxic conditions, yielding 4% pO 2 in a culture medium enriched with platelet-rich plasma (PRP). In the study, it was observed that PRP had a stimulatory effect on the gene expression of the markers COL2A1 and SOX9 [127][128][129]. Jahr et al applied 2.5% pO 2 in the cultivation of articular chondrocytes while proving the expression of the chondrogenic markers ACAN and COL2A1 and the reduction of expression of the dedifferentiation markers COL1A1 and COL3A1.…”
Section: Activation Factorsmentioning
confidence: 99%